Injuries in the first Croatian soccer division - Matkovic, B. R.; Radman, I.; Ruzic, L.; Barisic, V. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Soccer players in most world leagues have very condensed schedule and these games are played at high intensity. Dupont with his coworkers (2010) showed that recovery time between two soccer matches appears to be sufficient for maintaining the level of physical performance but is not long enough to secure a low injury rate. The injuries in soccer appear to be more frequent and even more dangerous. The aim of this study was to identify the specific soccer circumstances and immediate technical and tactical causes of injuries in training process and competition of elite Croatian soccer players. Methods: The study was conducted on the sample of 175 players from seven soccer clubs of the First Croatian Soccer Division at the beginning of the season 2010/2011 Croatian Championship. Soccer players were tested just before the start of regular practice through the written questionnaire. The questionnaire consisted of general questions about number of training sessions per week and their duration, number of games played in last two seasons and number and character of the injuries in the same period. Results and discussion: The results show that 40% off all injuries occur during autumn competitive period. Significantly more injuries were sustained due to exposure to training load (60%). The highest percentage of injuries was recorded in the phase of defence set (26%). According to the ball possession, the highest injury risk was recorded during immediate contact with the ball or fight for her possession. In 70% of all injuries, recorded injuring mechanism was the physical contact with an opponent. The most vulnerable parts of the body were ankles and knees, and the ligaments and muscles were the most affected tissues. As prevention, implementation of training process should take place under conditions of controlled load in order to reduce the number of training caused injuries. The number of injuries caused by direct physical duel with an opponent is significantly higher than in Western European leagues, and indicates the need to raise the player body`s hardiness and tactical maturity of team trainers.